The Interpreter and the Canadian Convention Refugee Hearing: Crossing the potentially life-threatening boundaries between “coccode-e-eh,” “cluck-cluck,” and “cot-cot-cot” - Barsky, Robert (TTR, 1993)
AbstractThe Interpreter and the Canadian Convention Refugee Hearing: Crossing the potentially life-threatening boundaries between "coccode-e-eh," "cluck-cluck," and "cot-cot-cot" — This paper discusses the obstacles facing interpreters and translators in inter-cultural situations with reference to Canadian Convention refugee hearings, taped in 1987. The author sets forth a theory of interpretation suited to the sometimes comical, but usually tragic elements of failed human interaction as they occur in legal hearings. The article begins with a comparison between a fictional rendering of failed communication from the work of Primo Levi, but then moves on to the plight of persecuted persons who have come to Canada to claim Convention refugee status. Obvious similarities emerge in a comparison of the two processes; but ultimately it is the language of persecution — silence, scars, tears, pleas, and impassioned cries — that is the most difficult to interpret and translate. Given the dynamics of inter-cultural legal discourse and the gravity of the issues at stake, the author argues for a broader mandate for the interpreter, such that s/he will also be permitted to act as a medium through which inter-cultural information can pass, rather than yet another grid into which pained words must fit.